Pliny the Elder and his writings about Mesopotamia - Hamed Al-Ukeli , Lect .Dr. Khalid (Basra studies journal, 2026)
In the early fifth century،This study deals with the biography of one of the famous writers of the ancient era, the Roman historian Caius Plinius Secundus, who is known as Pliny the Elder. This study aims to introduce the personality of the writer Pliny the Elder and his book "Natural History", due to its importance in writing the history of Mesopotamia during the ancient era in general and the Romanian era in particular. This study focused initially on the origins of Pliny the Elder, then introducing his book "Natural History" to finally arrive at presenting the valuable information mentioned in this book about the Mesopotamia region in his time.